A European innovation system in pharmaceuticals?. (1st January 2002) - Howells, Jeremy
This paper analyses the emergence and development of a European pharmaceutical system. In particular it reviews and assesses the influence of new institutional and regulatory frameworks on the creation of this pan-European pharmaceutical system. The paper then explores the implications of the formation of this process on our conceptualisation of the more specific "systems of innovation" approach.